The Resting Oxidized State of Small Laccase Analyzed with Paramagnetic NMR Spectroscopy. Issue 8 (19th March 2021) - Dasgupta, Rubin; Gupta, Karthick B. S. S.; de Groot, Huub J. M.; Ubbink, Marcellus
Abstract: The enzyme laccase catalyzes the reduction of dioxygen to water at the trinuclear copper center (TNC). The TNC comprises a type‐3 (T3) and a type‐2 (T2) copper site. The paramagnetic NMR spectrum of the small laccase from Streptomyces coelicolor (SLAC) without the substrate shows a mixture of two catalytic states, the resting oxidized (RO) state and the native intermediate (NI) state. An analysis of the resonances of the RO state is reported. In this state, hydrogen resonances only of the T3 copper ligands can be found, in the region of 12–22 ppm. Signals from all six histidine ligands are found and can be attributed to Hδ1, Hβ or backbone amide H N nuclei. Two sequence‐specific assignments are proposed on the basis of a second‐coordination shell variant that also lacks the copper ion at the T1 site, SLAC−T1D/Q291E. This double mutant is found to be exclusively in the RO state, revealing a subtle balance between the RO and the NI states. Abstract : Subtle balance : The tri‐nuclear copper center (TNC) of laccase reduces oxygen to water very efficiently via a complex multistep process. We report significant progress in deciphering the complicated paramagnetic spectrum of the nuclei around the TNC using tailored NMR experiments and second coordination shell mutagenesis. The resonances of spins near the copper ions may be used as spies to characterize motions in the active site during the catalytic cycle.